2012
DOI: 10.1089/ars.2011.4341
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisWhiB3: A Novel Iron–Sulfur Cluster Protein That Regulates Redox Homeostasis and Virulence

Abstract: Significance: Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), can persist in a latent state for decades without causing overt disease. Since latent Mtb is refractory to current antimycobacterial drugs, the discovery and characterization of the biological mechanisms controlling the entry, maintenance, and emergence from latent infection is critical to the development of novel clinical therapies. Recent Advances: Recently, Mtb WhiB3, a member of the family of intracellular iron-sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…185,[190][191][192] The expression of whiB3 is enhanced in macrophages and the mouse lung, indicating that M. tuberculosis regulates whiB3 expression in response to environmental signals associated with infection; this is supported by the findings that hypoxia and NO induced whiB3 expression. [193][194][195][196] Its role in virulence is clear-mice infected with a whiB3 null mutant showed increased survival.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…185,[190][191][192] The expression of whiB3 is enhanced in macrophages and the mouse lung, indicating that M. tuberculosis regulates whiB3 expression in response to environmental signals associated with infection; this is supported by the findings that hypoxia and NO induced whiB3 expression. [193][194][195][196] Its role in virulence is clear-mice infected with a whiB3 null mutant showed increased survival.…”
mentioning
confidence: 73%
“…Hence WhiB3 senses the redox state of the bacterium via the presence/absence of the iron-sulfur cluster and the propensity of the cysteine residues that ligate the iron-sulfur cluster to form intramolecular disulfide bonds under oxidizing conditions. 185,191 The physiological significance of the NO-reactivity of the WhiB3 iron-sulfur cluster has yet to be established.…”
mentioning
confidence: 99%
“…During infection, M. tuberculosis is exposed to oxygen and NO stress, which influence stability of the WhiB3 [4Fe-4S] cluster 84, 103 . In the presence of these stressors, the [4Fe-4S] cluster is degraded leading to an accumulation of apo-WhiB3.…”
Section: Iron-sulfur Cluster Regulators and Their Role In Bacterial Pmentioning
confidence: 99%
“…In the presence of these stressors, the [4Fe-4S] cluster is degraded leading to an accumulation of apo-WhiB3. Interestingly, this form of WhiB3 is able to undergo further post-translational modifications in response to redox stress, modulating DNA-binding activity 85, 103 . M. tuberculosis experiences redox stress during infection as a result of NADPH production following fatty acid β-oxidation 103, 104 .…”
Section: Iron-sulfur Cluster Regulators and Their Role In Bacterial Pmentioning
confidence: 99%
“…In vivo, whiB3 expression is upregulated in response to NO and an acidic extracellular pH. Seminal work by Singh et al [172] showed that [4Fe-4S] WhiB3 was sensitive to NO, with exposure enhancing site specific DNA binding and, in vivo, shifting propionate anabolism in favor of virulence determinants (polyketides, polyacyltrehaloses, sulfolipids, and phthiocerol dimycocerosates) and storage lipids (principally triacylglycerol) [172][173][174]. Remarkably, the WhiB3-dependent production of polyketide virulence determinants, in part, disrupts phagosomal maturation and acidification.…”
Section: Wbl Proteins In Mycobacteriamentioning
confidence: 99%